Development and application of a method for analysis of lufenuron in wheat flour by gas chromatography-mass spectrometry and confirmation of bio-efficacy against Tribolium castaneum (Herbst) (Coleoptera : Tenebrionidae) - Ahire, Kedar C.; Arora, Manjit S.; Mukherjee, Samindra N. (Journal of Chromatography B-Analytical Technologies in the Biomedical and Life Sciences, 2008)
A new analytical method using gas chromatography with mass spectrometry (GC-MS) for the quantitative determination of lufenuron, a benzoylphenylurea (BPU) class of insecticide, from wheat flour has been developed and applied for time-dependant residue monitoring in treated wheat flour. The analyte was extracted from wheat flour by a single step solid-liquid extraction by using ethyl acetate and subsequently cleaned up using the Primary Secondary Amine as a sorbent prior to GC-MS analysis. The present method provides sufficient sensitivity as reflected by the values of limit of detection (LOD) and limit of quantification (LOQ), 5 ng/mL (S/N similar to 3) and 50 ng/mL (the lowest validation point on the calibration curve), respectively. The calibration curve showed an excellent linearity in the concentration range of 50-1000 ng/mL (r(2) = 0.998). The average recovery for spiked samples at three concentrations (150, 300, and 450 ng/g) was 98.23 +/- 2.52% R.S.D. The method was applied for the determination of lufenuron residues in treated wheat flour samples. Simultaneous determination of bio-efficacy of lufenuron residues was also carried out against the red flour beetle, Tribolium castaneum to correlate the actual residual effect of lufenuron as detected by the analytical method, over a period of 3 months. The findings revealed that the residual concentration of lufenuron were neither uniform nor in descending order over a period of 3 months in wheat flour, possibly because of an uneven dispersal in the treated wheat which was subsequently milled into flour, as confirmed by GC-MS analysis. However, the residues of lufenuron were sufficient to produce 100% mortality of T. castaneum larvae up to 3 months. The results have been discussed in view of the potential of lufenuron as a candidate molecule for the control of stored product pests. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: bio-efficacy; GC-MS; lufenuron; method development; residue analysis; Tribolium castaneum; Wheat

Effect of sub-lethal concentrations of insect growth regulator, lufenuron on larval growth and development of Aedes aegypti - Salokhe, S. G.; Mukherjee, Samindra N.; Deshpande, S. G.; Ghule, V. P.; Mathad, J. R. (Current Science, 2010)
The effect of sub-lethal concentrations (LC20 = 0.0002 and 0.001 ppm, and LC40 = 0.002 and 0.02 ppm for II and IV instar larvae respectively) of a dispersible concentrate formulation of the insect growth regulator, lufenuron on larval growth and development of Aedes aegypti was studied. When II and IV instar larvae were subjected to the above-mentioned sub-lethal concentrations of lufenuron through the culture medium, there was a significant increase in the time taken for pupation (17.2 +/- 0.74 and 11.4 +/- 0.8 days for II and IV instar LC20-treated larvae respectively, and 19 +/- 0.89 and 14.6 +/- 1.0 days for II and IV instar LC40-treated larvae respectively). Also, there was increase in the time taken for adult emergence 3.8 +/- 0.83 and 5.4 +/- 0.83 days from pupation of LC40-treated II and IV instar larvae respectively). There was 28.1 +/- 2.06% and 43.59 +/- 0.87% reduction in pupation in LC20 of lufenuron-treated II and IV instar A. aegypti larvae respectively. Also, with LC20 of lufenuron-treated II and IV instar larvae there was 43.54 +/- 5.12% and 43.59 +/- 0.87% reduction in adult emergence respectively. Further, it was observed that II instar larvae treated with LC20 of lufenuron developed into 25.8 +/- 2.08% deformed adults. In LC40-treated II instar larvae there was 33.72 +/- 2.38% reduction in pupation and 63.44 +/- 4.76% reduction in adult emergence. Also, it was observed that there was 54.84 +/- 3.9% and 61.3 +/- 5.2% reduction in pupation and adult emergence respectively, in IV instar larvae treated with LC40 of lufenuron. The reduction in pupation of the IV instar larvae treated with LC40 of lufenuron was due to failure of the larvae to undergo pupation. These studies are fundamental to the use of lufenuron in A. aegypti management.
Keywords: Aedes aegypti; larval growth and development; lufenuron; sub-lethal concentration